Choroidal Ganglioneuroma and Orbital Plexiform Neurofibroma Presenting as Buphthalmos in an Infant With Neurofibromatosis Type 1. Issue 4 (July 2016) - Goyal, Sunali; Park, Abraham; Zeglam, Ahmaida; Brown, Harry; Pemberton, John D.
Abstract : Neurofibromatosis type 1 (NF-1) is an autosomal dominant familial tumor predisposition syndrome characterized by the growth of benign and malignant tumors involving the peripheral and central nervous system. In the following report, the authors describe a case of a 1-year-old child with NF-1, who underwent enucleation for a blind, proptotic, painful eye with subsequent histopathological examination revealing choroidal ganglioneuroma, a very rare entity. Abstract : Choroidalganglioneuroma discovered in a buphthalmic eye of a young infant with NF-1 who also harbored a large ipsilateral orbital plexiformneurofibroma. Review of prior cases of choroidalganglioneuromas demonstrates an association of chorodialganglioneuroma in patient with unexplained buphthalmos and NF-1.